The Glorious Fight - Provensen, Alice & Martin; Nang Chan Yeema (New York, USA Puffin Books, 1987)
A biography of the man whose fascination with flying machines produced the Bleriot XI, which in 1909 became the first heavier-than-air machine to fly the English Channel.
Keywords: Juvenile Nonfiction